Pemahaman Kristologis tentang Kemanusiaan Yesus Kristus dan Relevansinya bagi Umat Percaya - Adithya Putra Mayu Nugraha; Deva Anastasya; Enjelia Eva Talenta; Yolanda Agustina; Sarmauli Sarmauli (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to explore the understanding of Christology regarding the humanity of Jesus Christ and its relevance for believers. Using a qualitative literature review method, this research analyzes biblical texts and theological literature to examine Jesus' human nature, His salvific mission, and the practical application of His teachings. The findings indicate that Jesus Christ, as the God-man, demonstrated perfect human qualities including compassion, humility, honesty, and patience. His death and resurrection provide redemption from sin, fulfilling God's salvation plan. The study concludes that Christological understanding enables Christians to emulate Jesus' teachings in contemporary life through evangelism, love, and prayer. These findings offer significant implications for Christian education, church ministry, and the spiritual development of believers in maintaining a Christ-centered life.